Language as a phenomenon: Belarusian language in the context of diglossia - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2020)
It is possible to talk about language from the point of view of a linguist, but language is also a sociocultural phenomenon, and its development takes place in a social and political context. This, of course, applies to any of the languages, however, in relation to the Belarusian language it acquires many specific aspects. First of all, this concerns the situation of bilingualism (and bilingualism as closely related), within which, under the influence of socio-political factors, languages acquire unequal status, as a result of which their hierarchy is built. The historical development of the Belarusian language (in its contextual relationship with Russian) demonstrates serious deformations that it had to endure in the course of its evolution.
Keywords: Belarusian language; linguistic variability; social roles of language; vertical bilingualism; diglossia; status of languages; H-language (high language); L-language (low language); language hierarchy; exoglossity